Suitability of Visual Resource Assessment Procedure in Determining Public Perception of Malaysian Landscape Quality - Saidon, Mohd Nazri (2007)
The issue on who is responsible to determine whether visual landscape quality is good or bad, attractive or unattractive, and so forth is still in much debate. This research was conducted to investigate the preference between expert personnel and public in visual landscape quality. This is due to the problem whether either method being use by expert can represent public preferences. The hypothesis of this study is there is no significant difference in visuaI landscape quality preferences between the expert and public to the study area. The goal was to determine if the expert method (VRAP) is suitable in representing the public preferences for visual quality of Malaysian landscape. There are two groups of respondents, which are expert and public groups. The expert consists of ten ( ~ 1 0 r)e spondents conducted the field assessment by following strictly the expert method (VlUW) while the public respondents were shown thirty-six tests slide photographs (based on public method). These photographs were systematically taken at the site and the respondents were asked to rate their preferences for each photos. The scale of visual quality preference was given range fiom extremely attractive, attractive, little attractive, unattractive to extremely unattractive. The individual score (percentage ranking) of public assessment was then compared to the median (percentage ranking) of expert groups evaluation using non-parametric statistical analysis. At the same time, several statistical tests were also conducted to determine the pattern of expert and public preferences of visual quality assessment. Results indicated that there are significant difference of visual preference (p-value =O. 004) between the expert and public at the study site. This finding suggests that experts and public have difference perception of visual quality preference of Malaysian landscape. Therefore, the expert method (VRAP) is not able to represent public preferences in this study.